A SEMANTIC ANALYSIS OF THETA ROLE IN PRABOWO SUBIANTO'S PRESIDENTIAL INAUGURAL SPEECH - Panjaitan, Indra Purnawan; Mulyadi, Mulyadi (Universitas Islam Sumatera Utara, 2025)
This study examines the use of Theta roles in President Prabowo Subianto's inauguration speech delivered on October 20, 2024. Employing a qualitative descriptive method, the research investigates how Theta roles function within the framework of political communication. The data were derived from the official transcript of the speech. The analysis reveals that the Agent and Theme roles are the most frequently occurring, appearing in 83% and 66.6% of the relevant structures, respectively. The predominance of these roles underscores Prabowo’s rhetorical emphasis on action, leadership, and policy direction. These findings indicate that the speech serves not only as a medium for policy articulation but also as a strategic rhetorical tool aimed at building public trust and mobilizing support. This study contributes to a deeper understanding of linguistic patterns and argumentation strategies in Indonesian political discourse and offers a foundation for further exploration of Theta role application in political speech analysis.